Combined therapy of GABA and sitagliptin prevents high-fat diet impairment of beta-cell function. (1st January 2023) - Wang, Zhihong; Fan, Linling; Ni, Yunzhi; Wu, Di; Ma, Anran; Zhao, Ying; Li, Jia; Cui, Qiaoli; Zhou, Yue; Zhang, Li; Lou, Yan-Ru; Prud'homme, Gerald J.; et al.
Abstract: We recently demonstrated that combined therapy of GABA and sitagliptin promoted beta-cell proliferation, and decreased beta-cell apoptosis in a multiple low-dose streptozotocin (STZ)-induced beta-cell injury mouse model. In this study, we examined whether this combined therapy is effective in ameliorating the impairment of beta-cell function caused by high-fat diet (HFD) feeding in mice. Male C57BL/6J mice were fed normal chow diet, HFD, or HFD combined with GABA, sitagliptin, or both drugs. Oral drug daily administration was initiated one week before HFD and maintained for two weeks. After two weeks of intervention, we found that GABA or sitagliptin administration ameliorated the impairment of glucose tolerance induced by HFD. This was associated with improved insulin secretion in vivo. Notably, combined administration of GABA and sitagliptin significantly enhanced these effects as compared to each of the monotherapies. Combined GABA and sitagliptin was superior at increasing beta-cell mass, and associated Ki67 + and PDX-1 + beta-cell counts. In addition, we found that HFD-induced compensatory beta-cell proliferation was associated with increased activation of unfolded protein response (UPR), as indicated by BiP expression. This could be an important mechanism of compensatory beta-cell proliferation, and beta cells treated with GABA and sitagliptin showed greater UPR activation. Our results suggest that the combined use of these agents produces superior therapeutic outcomes. Highlights: Short term HFD induced compensatory β-cell proliferation and impaired insulin secretion. Combined therapy of GABA and sitagliptin improved glucose tolerance and insulin secretion in short-term HFD model. Combined therapy of GABA and sitagliptin promoted β-cell proliferation and increased β-cell mass in short-term HFD model. Combined therapy of GABA and sitagliptin activated UPR during short-term HFD.